PENGARUH DUKUNGAN ORGANISASI DAN KEADILAN IMBALAN TERHADAP KEPUASAN KERJA SOPIR KOPTAX NGURAH RAI - Dewi, Ni Putu Kartika Candra; Dewi, A.A. Sagung Kartika (E-Jurnal Manajemen, 2018)
In an organization, what triggers an employee morale to survive and provide great loyalty for the progress of the company has always been the goal for every company. This research was conducted on Koptax Ngurah Rai Bali. Number of respondents taken using simple random sampling technique as many as 255 taxi drivers as employees. The analysis technique used is multiple linear regression. The results of analysis testing in this study indicate that organizational support has a positive effect on job satisfaction. Justice rewards have a positive effect on job satisfaction. The results of the analysis obtained in this study, it is hoped Koptax Ngurah Rai management can pay more attention to organizational support and equity benefits experienced by employees, so that the level of job satisfaction perceived by employees increases.